The Effects of Perceived Risk, Personality Trait, and Social Media on Experience Value and Satisfaction- A Study on Water Adventure Recreation in Taiwan (Global Journal of Management and Business Research, 2021)
This paper utilized a questionnaire to study the influence of perceived risk, personality trait, and social media on experience value and satisfaction on water adventure recreation activities in Taiwan. There were 314 surveyors who took part in water adventure recreation. PLS measurement of the model GOF was 0.461, while the SRMR was 0.087, reaching a significant level. The whole model with 72.6% of satisfaction shows that the model is excellent.
Keywords: perceived risk; personality trait; social media; adventure recreation; partial least squares (PLS)